A method for distinguishing the surface polarity of two-dimensional Bi2O2Se using circularly polarized photocurrent
By measuring the circularly polarized photocurrent of Bi2O2Se nanosheets with the gate pressure of ionic liquid, the problem of judging the surface polarity of two-dimensional Bi2O2Se materials is solved, and accurate distinction and non-destructive detection are achieved.
Patent Information
- Application Number
- CN202211735781.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-31
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2042-12-31
AI Technical Summary
There are challenges in judging the surface polarity of two-dimensional Bi2O2Se materials, and it is difficult for the prior art to accurately distinguish their surface cutoff types.
By measuring the change trend of the circularly polarized photocurrent of Bi2O2Se nanosheets with the gate pressure of the ionic liquid, the initial surface polarization polarization is distinguished by the changing characteristics of the circularly polarized photocurrent.
The accurate distinction between the surface polarity of two-dimensional Bi2O2Se materials is achieved. The method is simple and easy to implement, the application range is wide, and there is no damage to the sample surface.
Smart Images

Figure CN116223927B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of spin electronics, and in particular to a method for distinguishing the surface polarity of two-dimensional Bi2O2Se by circularly polarized photocurrent. Background Art
[0002] As a high-mobility layered two-dimensional material, Bi2O2Se has a suitable band gap, a very large photoresponsivity and an ultrafast response speed, and has excellent development potential in the field of optoelectronic devices. In addition, it exhibits ultra-high water-oxygen stability, which has great advantages in practical applications. In addition, through low-temperature magnetotransport measurements, it was found that there is a strong spin-orbit coupling effect in Bi2O2Se, which lays the foundation for the research of Bi2O2Se in the field of spin electronics and spin optoelectronic devices.
[0003] Bi2O2Se is a typical layered oxidized chalcogenide. Its crystal structure consists of alternating compensated cations (Bi2O2) n 2n+ and anion (Se) n 2n- The two-dimensional Bi2O2Se is composed of alternating stacking and maintains a layered structure with weak electrostatic interactions. During the growth of two-dimensional Bi2O2Se, its development mode is layer-by-layer growth, so that the outermost surface is either cut off by the positively charged Bi layer or the negatively charged Se layer, which introduces different surface polarities to the Bi2O2Se surface. The opposite surface polarities cause surface energy band bending in different directions, and introduce different forms of Rashba-type surface states between the band gaps, and their Rashba spin-orbit coupling coefficients are opposite, so that the two surface cutoff types of Bi2O2Se have different surface electronic band structures, and the circularly polarized photocurrents they generate are in opposite directions. Since the cutoff type is random during the surface growth of Bi2O2Se, it becomes difficult to determine its surface cutoff type, which brings challenges to the research of Bi2O2Se in spin electronics. Summary of the invention
[0004] The purpose of the present invention is to provide a method for distinguishing the surface polarity of two-dimensional Bi2O2Se by circularly polarized photocurrent, which has accurate measurement, is simple and easy to operate, and has a wide range of applications.
[0005] To achieve the above object, the technical solution adopted by the present invention is: a method for distinguishing the surface polarity of two-dimensional Bi2O2Se by circularly polarized photocurrent, comprising the following steps:
[0006] Step S1: growing Bi2O2Se nanosheets on a substrate in a tube furnace by chemical vapor deposition;
[0007] Step S2: fabricating a contact electrode on the nanosheet by ultraviolet lithography and thermal evaporation technology, and fabricating a gate electrode at a predetermined distance from the nanosheet;
[0008] Step S3: a ring bracket is arranged on the substrate to form a groove on the surface of the nanosheet, the groove covers the entire nanosheet and part of the gate electrode, an ionic liquid is added to the groove and a cover glass is placed on the groove for packaging to form a test structure; the ionic liquid simultaneously covers the entire surface of the nanosheet and contacts the gate electrode, and the gate electrode applies a gate voltage to the surface of the nanosheet through the ionic liquid;
[0009] Step S4: Building an experimental optical path: The laser light source emits laser light, which passes through a chopper, an optical attenuator, a polarizer, and a quarter-wave plate in sequence; the polarized light is focused by a lens and irradiated on the nanosheet of the test structure to form a light spot; the macro camera is used to align the light spot position so that it completely covers the nanosheet;
[0010] Step S5: inputting the photocurrent collected by the contact electrode into the preamplifier, and then inputting the phase-locked amplifier from the preamplifier, the phase-locked amplifier signal enters the data acquisition card and is collected by the computer; applying the gate voltage through the electrometer, and the electrometer and the preamplifier share the same ground;
[0011] Step S6: Testing the photocurrent in Bi2O2Se nanosheets as a function of quarter wave plate rotation angle at room temperature The change curve of the circular polarization photocurrent C is extracted;
[0012] Step S7: Apply a gate voltage of 0 to -2V, repeat step S6 every time the gate voltage increases by a set value, and record the extracted C value to observe the change trend of C with the gate voltage; if the C value increases linearly with the increase of the gate voltage, it means that the initial surface polarity of Bi2O2Se is Bi atom cutoff, and its initial surface is positively charged; if the C value first decreases to 0 with the gate voltage, reverses its sign and then continues to increase in the opposite direction, it means that the initial surface polarity of Bi2O2Se is Se atom cutoff, and its initial surface is negatively charged.
[0013] Furthermore, in the step S1, the Bi2O2Se nanosheets are of a medium single crystal structure and have a thickness between 5 and 50 nanometers.
[0014] Furthermore, in step S3, the annular bracket is a polycarbonate bracket, the polycarbonate bracket and the substrate are sealed by epoxy resin, and the polycarbonate bracket and the cover glass are also encapsulated by epoxy resin to achieve sealing of the entire test structure.
[0015] Furthermore, in step S4, the laser light source adopts a diode-pumped solid-state laser with a wavelength of 1064 nm.
[0016] Furthermore, in step S4, the laser power is 100 mW, the diameter of the light spot is less than 100 μm, the laser is incident from the xz plane, the incident angle is 30°, and the photocurrent is measured in the x direction; the polarization direction of the polarizer is 45° to the horizontal plane, and the frequency of the chopper is set to 229 Hz.
[0017] Furthermore, in step S5, the reference frequency of the phase-locked amplifier is 229 Hz, which is consistent with the chopper.
[0018] Furthermore, in step S6, the photocurrent in the Bi2O2Se nanosheet is measured at room temperature as the quarter wave plate angle changes. The change curve of the circularly polarized photocurrent is extracted by the following phenomenological formula;
[0019]
[0020] in, represents the component of circularly polarized photocurrent induced by HDPC; Item and It comes from the photocurrent component induced by the linearly polarized photocurrent effect and the linearly polarized photon drag effect; J0 represents the photocurrent component that is independent of polarization, which is induced by the linearly polarized photovoltaic effect, photon drag effect, thermoelectric effect, photovoltaic effect and Danby effect; through fitting, the circularly polarized photocurrent C is obtained.
[0021] Furthermore, in step S7, an ionic liquid gate rather than a solid dielectric layer is used to apply the gate voltage.
[0022] Compared with the prior art, the present invention has the following beneficial effects: providing a method for distinguishing the surface polarity of two-dimensional Bi2O2Se by circularly polarized photocurrent, which can simply distinguish the surface polarity of two-dimensional Bi2O2Se by testing the change trend of the circularly polarized photocurrent of Bi2O2Se nanosheets with the gate voltage of ionic liquid, and does not damage the sample surface. The present invention has accurate measurement results, is simple and easy to operate, has low cost, and is widely applicable to materials with polar surfaces and spin-orbit coupling. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Schematic diagram of the experimental device for growing Bi2O2Se nanosheets in an embodiment of the present invention.
[0024] Figure 2 Schematic diagram of a test structure in an embodiment of the present invention.
[0025] Figure 3 Schematic diagram of a circularly polarized light path and a test system in an embodiment of the present invention.
[0026] Figure 4It is the polarization-dependent photocurrent component obtained by fitting the curve of photocurrent variation with quarter-wave plate rotation angle in the embodiment of the present invention.
[0027] Figure 5 1 is a curve showing the variation of the circularly polarized photocurrent amplitude with the ionic liquid gate voltage in an embodiment of the present invention, and the insets show the surface band bending produced by the ionic liquid gate and the polarity of the surface charge accumulation layer. DETAILED DESCRIPTION
[0028] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.
[0029] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0030] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0031] This embodiment provides a method for distinguishing the surface polarity of two-dimensional Bi2O2Se by circularly polarized photocurrent, comprising the following steps:
[0032] Step S1: Growing Bi2O2Se nanosheets on a substrate in a tube furnace by chemical vapor deposition.
[0033] Among them, the Bi2O2Se nanosheets are single crystal structures with a thickness between 5 and 50 nanometers.
[0034] In this embodiment, the substrate used for growth is a high-quality, high-flatness mica substrate with a specification of 1.5×2 cm; the upper surface of the mica is torn off by mechanical stripping before use to obtain a freshly cracked clean surface. The evaporation sources used are 99.999% pure Bi2Se3 powder and 99.999% Bi2O3 powder, 0.02g and 0.04g of which are weighed respectively and placed at both ends of a 10cm long quartz boat. The mica substrate is also placed in the furnace, and its placement diagram is shown in the figure. Figure 1 As shown in the figure, the position of Bi2O3 is located in the center of the heating temperature zone of the tube furnace, the Bi2Se3 powder is located 8 cm upstream of the center, the left edge of the mica substrate is located 10.5 cm downstream of the center, and the growth position of the Bi2O2Se nanosheet appears 11 cm to 11.5 cm downstream of the center, as shown in the figure. Figure 1 shown.
[0035] Before increasing the temperature of the furnace zone, the tubular furnace needs to be purged to remove excess oxygen in the growth environment. The specific operation is to evacuate the tube to a vacuum (0.5Pa), then fill it with high-purity argon to standard atmospheric pressure, and repeat this step 3 to 5 times. Use argon as the growth carrier gas, control the gas flow rate to 200sccm; by controlling the fine-tuning valve, keep the gas pressure in the furnace at 450-500torr. Then, set the heating parameters, first set the temperature from room temperature to 680℃ at a heating rate of 25℃ / min; then, maintain 680℃ for twenty minutes. When the furnace temperature drops to room temperature, take out the grown sample.
[0036] The size of the grown samples was about 100 μm and the thickness was 25 nm.
[0037] Step S2: A contact electrode is fabricated on the nanosheet by ultraviolet lithography and thermal evaporation technology, and a gate electrode is fabricated at a position 1 mm away from the nanosheet.
[0038] In this embodiment, the UV lithography process and electrode manufacturing method are as follows: first, spin-coat the negative photoresist on the sample surface with the spin coating parameters of 5000r / min for 150s; then, pre-bake for 120s at 85°C; then, align the positions of the nanosheet and the mask under a microscope for precise exposure with an exposure time of 9.8s; then, post-bake for 120s at 110°C; develop the exposed sample with a development time of 60s; finally, wash the sample with deionized water to remove the residual developer on the surface.
[0039] After photolithography, 100 nm of gold was evaporated on the sample surface by thermal evaporation. The pressure in the chamber was maintained at 10 -5 Pa. Finally, the sample was immersed in a special degumming solution to remove the photoresist, exposing the nanosheet and electrode pattern, and then the degumming solution was washed off with deionized water. The channel width of the device is 20μm, and a gate electrode 1mm away from the sample is made near the contact electrode. After making the gold electrode, the electrode is led out through silver paste and silver wire, and thermally annealed for 120min under vacuum conditions at 120℃ to solidify the silver paste and enhance contact.
[0040] Step S3: a ring bracket is arranged on the substrate to form a groove on the surface of the nanosheet, the groove covering the entire nanosheet and part of the gate electrode; the groove is filled with ionic liquid and covered with a cover glass for packaging to form a test structure, such as Figure 2 As shown in Figure 1, the ionic liquid covers the entire surface of the nanosheet and contacts the gate electrode, which applies a gate voltage to the surface of the nanosheet through the ionic liquid. The manufacturing process ensures that the entire test structure is sealed.
[0041] In this embodiment, the annular bracket is a polycarbonate bracket, and the polycarbonate bracket and the substrate are sealed by epoxy resin, and the polycarbonate bracket and the cover glass are also encapsulated by epoxy resin to achieve sealing of the entire test structure.
[0042] Step S4: Build the experimental optical path: The laser light source emits laser light, which passes through the chopper, optical attenuation plate, Glan Taylor prism (polarizer) and quarter wave plate in sequence. The rotation of the quarter wave plate can change the polarization of light, making it change periodically from linear polarized light to left-handed polarized light to linear polarized light to right-handed polarized light. The polarized light is focused by the lens and irradiated on the nanosheet of the test structure to form a light spot. The macro camera is used to align the light spot position so that it completely covers and irradiates the Bi2O2Se nanosheet. Figure 3 shown.
[0043] In this embodiment, the laser light source uses a diode-pumped solid-state laser with a wavelength of 1064nm. The laser power is 100mW, the diameter of the spot is less than 100μm, the laser is incident from the xz plane, the incident angle is 30°, and the photocurrent is measured in the x direction; the polarization direction of the polarizer is 45° to the horizontal plane, and the frequency of the chopper is set to 229Hz. The magnification of the macro camera is 1000.
[0044] Step S5: input the photocurrent collected by the contact electrode into the preamplifier, and then input the phase-locked amplifier from the preamplifier. The phase-locked amplifier signal enters the data acquisition card and is collected by the computer; the gate voltage is applied through the electrometer, and the electrometer and the preamplifier share a common ground.
[0045] In this embodiment, the reference frequency of the lock-in amplifier is 229 Hz, which is consistent with the chopper.
[0046] Step S6: Testing the photocurrent in Bi2O2Se nanosheets as a function of quarter wave plate rotation angle at room temperature The change curve of the circularly polarized photocurrent C is extracted.
[0047] In this embodiment, the photocurrent in the Bi2O2Se nanosheet is measured at room temperature as the quarter-wave plate angle changes. The circularly polarized photocurrent is extracted by the following phenomenological formula: Figure 4 shown.
[0048]
[0049] in, represents the component induced by circularly polarized photocurrent (HDPC); Item and It comes from the photocurrent component induced by the linearly polarized photocurrent effect and the linearly polarized photon drag effect; J0 represents the photocurrent component that is independent of polarization, which is induced by the linearly polarized photovoltaic effect, photon drag effect, thermoelectric effect, photovoltaic effect and Danby effect; through fitting, the circularly polarized photocurrent C is obtained.
[0050] Step S7: Apply a gate voltage of 0 to -2V, repeat step S6 every time the gate voltage increases by 0.2V, and record the extracted C value to observe the change trend of C with the gate voltage; if the C value increases linearly with the increase of the gate voltage, it means that the initial surface polarity of Bi2O2Se is Bi atom cutoff, and its initial surface is positively charged; if the C value first decreases to 0 with the gate voltage, reverses its sign and then continues to increase in the opposite direction, it means that the initial surface polarity of Bi2O2Se is Se atom cutoff, and its initial surface is negatively charged.
[0051] In this embodiment, an ionic liquid gate rather than a solid dielectric layer is used to apply the gate voltage.
[0052] The principle of circularly polarized photocurrent to determine the initial surface polarity of Bi2O2Se is as follows: First, Bi2O2Se has surface polarity, and the band structures of surfaces with different polarities are different, with opposite Rashba spin-orbit coupling coefficients, and the circularly polarized photocurrents generated under the same irradiation conditions are also opposite in direction. Secondly, the ionic liquid gate can effectively regulate the density of electrons on the sample surface and the bending of the surface energy band. At the ionic liquid / semiconductor interface, the ionic liquid gate can be regarded as a nano-gap capacitor with huge capacitance, which can accumulate the charge on the Bi2O2Se surface to a high density that cannot be achieved by traditional solid gate dielectrics. Furthermore, the ionic liquid gate can affect the Rashba spin splitting of electrons on the sample surface, so that it can effectively regulate the circularly polarized photocurrent generated by the surface state of Bi2O2Se.
[0053] When a negative voltage is applied to the gate, the cations in the ionic liquid move toward the gate and form a positively charged charge accumulation layer on the surface of Bi2O2Se, causing the surface energy band of Bi2O2Se to bend upward. If the initial surface polarity of Bi2O2Se is positive (Bi cutoff surface), the intrinsic energy band bending is consistent with the effect brought by the gate, and the gate voltage will enhance the Rashba spin splitting of the surface electrons, that is, enhance the circularly polarized photocurrent. If the initial surface polarity of Bi2O2Se is negative (Se cutoff surface), the surface electric field and surface energy band bending caused by the ionic liquid gate offset the intrinsic energy band bending, resulting in a decrease in the circularly polarized photocurrent. When the surface electric field effect is greater than the effect of the intrinsic energy band bending, the Rashba spin-orbit coupling coefficient flips and the circularly polarized photocurrent reverses its sign; further increasing the surface electric field, the circularly polarized photocurrent increases with the enhancement of the Rashba spin splitting caused by the electric field.
[0054] like Figure 5 As shown in the figure, in this embodiment, the circularly polarized photocurrent decreases first for negative gate voltage, and then continues to increase after flipping the sign, indicating that the initial surface polarity of the sample is negative, the Se atomic layer is cut off, and the intrinsic surface energy band is bent downward. The inset shows the surface band bending generated by the ionic liquid gate and the polarity of the surface charge accumulation layer.
[0055] In summary, the present invention provides a simple and easy-to-operate method, which distinguishes the initial surface polarity and intrinsic band bending of the two-dimensional Bi2O2Se material by judging the change trend of the circularly polarized photocurrent amplitude with the ionic liquid gate. In addition, the advantage of this method is that it is generally applicable to spin-orbit coupled materials with surface polarity and is a non-destructive detection method.
[0056] Those skilled in the art will appreciate that the embodiments of the present application may be provided as methods, systems, or computer program products. Therefore, the present application may adopt the form of a complete hardware embodiment, a complete software embodiment, or an embodiment in combination with software and hardware. Moreover, the present application may adopt the form of a computer program product implemented in one or more computer-usable storage media (including but not limited to disk storage, CD-ROM, optical storage, etc.) that include computer-usable program code.
[0057] The present application is described with reference to the flowcharts and / or block diagrams of the methods, devices (systems), and computer program products according to the embodiments of the present application. It should be understood that each process and / or box in the flowchart and / or block diagram, as well as the combination of the processes and / or boxes in the flowchart and / or block diagram, can be implemented by computer program instructions. These computer program instructions can be provided to a processor of a general-purpose computer, a special-purpose computer, an embedded processor, or other programmable data processing device to generate a machine, so that the instructions executed by the processor of the computer or other programmable data processing device generate instructions for implementing the processes in the flowchart and / or block diagram. Figure 1 A process or multiple processes and / or boxes Figure 1 A device that provides the functions specified in a block or multiple blocks.
[0058] These computer program instructions may also be stored in a computer-readable memory capable of directing a computer or other programmable data processing device to operate in a specific manner, so that the instructions stored in the computer-readable memory produce an article of manufacture comprising an instruction device, which implements the process Figure 1 A process or multiple processes and / or boxes Figure 1 A function specified in one or more boxes.
[0059] These computer program instructions can also be loaded onto a computer or other programmable data processing device so that a series of operating steps are executed on the computer or other programmable device to produce a computer-implemented process, thereby providing instructions for implementing the process. Figure 1 A process or multiple processes and / or boxes Figure 1 A step that specifies a function in one or more boxes.
[0060] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.
Claims
1. A method for distinguishing the surface polarity of two-dimensional Bi2O2Se by circularly polarized photocurrent, characterized in that: The following steps are involved: Step S1: growing Bi2O2Se nanosheets on a substrate in a tube furnace by chemical vapor deposition; Step S2: fabricating a contact electrode on the nanosheet by ultraviolet lithography and thermal evaporation technology, and fabricating a gate electrode at a predetermined distance from the nanosheet; Step S3: a ring bracket is arranged on the substrate to form a groove on the surface of the nanosheet, the groove covers the entire nanosheet and part of the gate electrode, an ionic liquid is added to the groove and a cover glass is placed on the groove for packaging to form a test structure; the ionic liquid simultaneously covers the entire surface of the nanosheet and contacts the gate electrode, and the gate electrode applies a gate voltage to the surface of the nanosheet through the ionic liquid; Step S4: Building an experimental optical path: The laser light source emits laser light, which passes through a chopper, an optical attenuator, a polarizer, and a quarter-wave plate in sequence; the polarized light is focused by a lens and irradiated on the nanosheet of the test structure to form a light spot; the macro camera is used to align the light spot position so that it completely covers the nanosheet; Step S5: inputting the photocurrent collected by the contact electrode into the preamplifier, and then inputting the phase-locked amplifier from the preamplifier, the phase-locked amplifier signal enters the data acquisition card and is collected by the computer; applying the gate voltage through the electrometer, and the electrometer and the preamplifier share the same ground; Step S6: Testing the photocurrent in Bi2O2Se nanosheets as a function of quarter wave plate rotation angle at room temperature The change curve of the circular polarization photocurrent C is extracted; Step S7: Apply a gate voltage of 0 to -2V, repeat step S6 every time the gate voltage increases by a set value, and record the extracted C value to observe the change trend of C with the gate voltage; if the C value increases linearly with the increase of the gate voltage, it means that the initial surface polarity of Bi2O2Se is Bi atom cutoff, and its initial surface is positively charged; if the C value first decreases to 0 with the gate voltage, reverses its sign and then continues to increase in the opposite direction, it means that the initial surface polarity of Bi2O2Se is Se atom cutoff, and its initial surface is negatively charged.
2. The method for distinguishing the surface polarity of two-dimensional Bi2O2Se by circularly polarized photocurrent according to claim 1, characterized in that: In the step S1, the Bi2O2Se nanosheets are single crystal structures and have a thickness between 5 and 50 nanometers.
3. The method for distinguishing the surface polarity of two-dimensional Bi2O2Se by circularly polarized photocurrent according to claim 1, characterized in that: In step S3, the annular bracket is a polycarbonate bracket, and the polycarbonate bracket and the substrate are sealed by epoxy resin, and the polycarbonate bracket and the cover glass are also encapsulated by epoxy resin to achieve sealing of the entire test structure.
4. The method for distinguishing the surface polarity of two-dimensional Bi2O2Se by circularly polarized photocurrent according to claim 1, characterized in that: In step S4, the laser light source adopts a diode-pumped solid-state laser with a wavelength of 1064 nm.
5. The method for distinguishing the surface polarity of two-dimensional Bi2O2Se by circularly polarized photocurrent according to claim 1, characterized in that: In step S4, the laser power is 100 mW, the diameter of the light spot is less than 100 μm, the laser is incident from the xz plane, the incident angle is 30°, and the photocurrent is measured in the x direction; the polarization direction of the polarizer is 45° to the horizontal plane, and the frequency of the chopper is set to 229 Hz.
6. The method of distinguishing the surface polarity of two-dimensional Bi2O2Se by circularly polarized photocurrent according to claim 1, characterized in that: In step S5, the reference frequency of the phase-locked amplifier is 229 Hz, which is consistent with the chopper.
7. The method of distinguishing the surface polarity of two-dimensional Bi2O2Se by circularly polarized photocurrent according to claim 1, characterized in that: In step S6, the photocurrent in the Bi2O2Se nanosheet is measured at room temperature as the function of the quarter wave plate rotation angle The change curve of the circularly polarized photocurrent is extracted by the following phenomenological formula; in, represents the component of circularly polarized photocurrent induced by HDPC; Item and It comes from the photocurrent component induced by the linearly polarized photocurrent effect and the linearly polarized photon drag effect; J0 represents the photocurrent component that is independent of polarization, which is induced by the linearly polarized photovoltaic effect, photon drag effect, thermoelectric effect, photovoltaic effect and Danby effect; through fitting, the circularly polarized photocurrent C is obtained.
8. The method of distinguishing the surface polarity of two-dimensional Bi2O2Se by circularly polarized photocurrent according to claim 1, characterized in that: In the step S7, the ionic liquid grid is used to apply the grid voltage.
Citation Information
Patent Citations
Compound with quantum interference effect and preparation method of vertical monomolecular field effect transistor integrated device comprising compound
CN112582540A
Measurement of local electrochemical process by differential reflectometery
US10962470B1